PENGARUH IKLAN ROKOK TERHADAP PERILAKU MEROKOK REMAJA DI DAERAH KOTA DAN DESA KABUPATEN PAMEKASAN - FILDZA FADHILA; Sri Widati; Mohammad Fatah (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2021)
Background: Data shows that smoking behavior in adolescents in Indonesia is a health problem that still deserves to be considered. Data shows that the prevalence of smoking in the population aged 10-18 in 2013-2018 in Indonesia has increased, namely Riskesdas 2013 (7.2%), Riskesdas 2016 (8.8%), and Riskesdas 2018 (9.1%). Pamekasan is one of the regencies in Indonesia that has a teen smoking rate of 25.64% (Riskesdas, 2018) with outdoor cigarette advertisements that are still scattered, especially in urban areas. Purpose: Analyzing the influence of cigarette advertising in Pamekasan Regency, by emphasizing comparisons in urban areas and village areas in Pamekasan Regency.. Method: This study is an observational study. In terms of time, the study was cross-sectional because the data collection, which includes free variables and bound variables, was conducted over a period of time. Sampling through online questionnaires by random methods. Results: There is a significant influence between the role of cigarette advertising on adolescent behavior in urban areas with a value of p = 0.029 (OR 2.718 95% CI 1,110-6,652). There was no influence on adolescents in rural areas. Conclusion: A communication message that can affect adolescent smoking behavior in urban areas is cigarette advertising, regardless of how many times the frequency of exposure.